An Assessment of Retention Pond Conditions in Housing Area at Batu Pahat, Johor - Hilary Muyan, Adam Chaing; Nurdalila Saji (Progress in Engineering Application and Technology, 2025)
Due to fast development and alterations in climatic patterns, flooding has become a longstanding problem in Malaysia, especially in urban residential regions. Retention ponds play an essential role in the management of stormwater runoffs and reduction of flood risks. This is an evaluation of the existing conditions, and the performance of retention ponds located in residential subdivisions within Batu Pahat, Johor, as outlined by the Urban Stormwater Management Manual (MSMA), Second Edition. The aim of the research is to identify whether these ponds are properly designed and work effectively as a flood mitigation mechanism. An evaluation checklist, observations on site, and supportive information were used to assess five preselected ponds. Design compliance, hydrological performance, environmental integration, maintenance practices and urban suitability were among the key evaluation criteria. The results indicated that the pond performance was quite variable with the Taman Seroja Indah and Taman Sri Mulia being mostly compliant, particularly with peak flow capacity handling and maintenance access. Contrastingly, Taman Mulia Indah and Taman Permata had been brought up through stark losses like a shoddily constructed drainage system, severe proliferation, and a lack of safety precautions, amping up the threats of flood and negative environmental impact. The ponds close to the routes and the parks appeared to be more accessible and well-placed in urban planning. The research findings are that not all the ponds are up to MSMA standards therefore need to be upgraded immediately. Improved design, frequent maintenance, and incorporating Sustainable Drainage Systems (SuDS) are needed to both increase the resilience to flooding in urban areas and facilitate policy towards sustainable water management.